Endoscopic Nasogallbladder Drainage Combined with Laparoscopic Surgery for Type I Mirizzi Syndrome with Acute Cholecystitis: A Case Series Report - Wei Han; Qing Yue; Kai Liu; Jian-ji Ke; Ling-yu Meng; Ya-hui Liu (Gastroenterology Research and Practice)
Objective. To investigate the safety and feasibility of endoscopic nasogallbladder drainage (ENGBD) combined with laparoscopic surgery for Mirizzi syndrome type I with acute cholecystitis. Methods. An analysis of 4 patients with type I Mirizzi syndrome with acute cholecystitis admitted to the First Hospital of Jilin University. Results. The patients underwent ENGBD, and laparoscopic surgery was evaluated postoperatively. All four patients successfully recovered from this combined surgical approach. Conclusion. The combination of ENGBD and laparoscopic surgery is safe and feasible for the treatment of patients with type I Mirizzi syndrome accompanied by acute cholecystitis. This approach may reduce the traumatic stress on patients and is worthy of widespread implementation.